Ecotourism Potentiality in the Dulahazra Safari Park, Bangladesh - Hossen, A; Ahsan, MF; Kamruzzaman, M (Journal of Environmental Science and Natural Resources, 2015)
In this research we explore the potentiality of ecotourism in a safari park as a new concept under South-Asian model with dynamic perspective comparing to other ecotourism destinations in Bangladesh. The research reveals that Safari Park is not only spotlighted ecotourism activities for recreation but it also plays a vital role to protect natural pristine with rich biological diversity. Besides, Safari Park concept in Bangladesh considered as a revenue source for government and socio-economic benefits to the local communities. It is, however, resource to students as well as researchers. DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22170 J. Environ. Sci. & Natural Resources, 7(1): 189-196 2014